Crohn's disease: The experience of living with a chronic illness - Sofía García-Sanjuán; Manuel Lillo-Crespo; Ángela Sanjuán-Quiles; Miguel Richart-Martínez (Instituto Nacional de Salud Pública, 2016)
Objective. To explore the experiences of people with Crohn disease (CD), their life-changing events, the impact on their lives and the strategies used to cope with it. Materials and Methods. Qualitative study. In-depth interviews were carried out on 10 people affected by the disease in the province of Alicante (Spain). The collection, processing and analysis of data was performed using some phenomenological elements. Results. The experiences of those affected can be classified into four main areas: recognition of the illness; perceived consequences of the disease itself by CD affected patients; disease management, and the search for support. Conclusions. Knowledge of the life experience of people affected by CD appears to be essential for the effective management of chronic illnesses when planning specific health treatment programs.